2022
DOI: 10.1111/nph.18397
|View full text |Cite
|
Sign up to set email alerts
|

An ABA‐serotonin module regulates root suberization and salinity tolerance

Abstract: Suberin in roots acts as a physical barrier preventing water/mineral losses. In Arabidopsis, root suberization is regulated by abscisic acid (ABA) and ethylene in response to nutrient stresses. ABA also mediates coordination between microbiota and root endodermis in mineral nutrient homeostasis. However, it is not known whether this regulatory system is common to plants in general, and whether there are other key molecule(s) involved.We show that serotonin acts downstream of ABA in regulating suberization in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…In addition, we also found several aspects of metabolism to be altered. For example, we find a protein cluster related to suberin biosynthesis (Figure 5 C ), which is consistent with suberin being reported to prevent root water loss (46, 47). We also find phenylpropanoid biosynthetic proteins to be a large portion of Cluster 4 (Figure 5 C ), with their accumulation having been related to abiotic stress resistance in apple (48) and wheat (49).…”
Section: Resultssupporting
confidence: 88%
“…In addition, we also found several aspects of metabolism to be altered. For example, we find a protein cluster related to suberin biosynthesis (Figure 5 C ), which is consistent with suberin being reported to prevent root water loss (46, 47). We also find phenylpropanoid biosynthetic proteins to be a large portion of Cluster 4 (Figure 5 C ), with their accumulation having been related to abiotic stress resistance in apple (48) and wheat (49).…”
Section: Resultssupporting
confidence: 88%
“…Recently, we found that serotonin is a negative regulator of salt tolerance in plants and OsT5H knockout could significantly increase tolerance to salinity. 72 The deficiency of serotonin in rice plants could have secondary effect on other organisms in the paddy ecosystem. In addition to the increased resistance to insect pests BPH and SSB, Arase et al 73 showed increased resistance to Magnaporthe grisea under light.…”
Section: The Tradeoffs Of Ost5h Knockoutmentioning
confidence: 99%
“…An increasing number of studies demonstrate that serotonin acts as a vital signaling molecule in modulating nearly all aspects of plant growth and development, such as seed formation, root growth and development, fruit ripening, and senescence [8,9,12]. In addition, the roles of serotonin in the plant response to several abiotic stresses such as UV-B stress, cold, salinity, drought, heavy metals, and thermal stress are also well characterized [9,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%